Prenatal Beginnings for Better Health - Maged Costantine (Frontiers Research Topics, 2018)
Pregnancy has significant short- and long-term health impacts for mother and child, which may lead to pediatric- and adult-onset diseases. Understanding these gestational origins of disease and currently existing platforms for prenatal care has resulted in significant advances to detect and prevent adverse maternal and fetal outcomes. Existing and emerging prenatal interventions that are instituted at critical times in gestation take advantage of unique therapeutic windows and provide an opportunity to modify the risks. This research topic encompasses a variety of approaches and interventions, such as maternal screening for fetal disease, advanced fetal imaging, biomarker development, stem cell or gene therapies, and others.